Assessment of the adequacy of oxygen delivery. Issue 5 (October 2016) - Mayer, Katherine; Trzeciak, Stephen; Puri, Nitin K.
Abstract : Purpose of review: This article reviews the recent literature pertaining to assessment of the adequacy of oxygen delivery in critically ill patients with circulatory shock. Recent findings: The assessment of the adequacy of oxygen delivery has traditionally involved measurement of lactate, central (or mixed) venous oxygen saturation (ScvO2 ), and global hemodynamic markers such as mean arterial pressure and cardiac index. The search for noninvasive, reliable, and sensitive methods to detect derangements in oxygen delivery and utilization continues. Recent studies focus on near-infrared spectroscopy (NIRS) to assess regional tissue oxygenation, as well as bedside ultrasound techniques to assess the macrovascular hemodynamic factors in oxygen delivery. Summary: In this article, we review physiologic principles of global oxygen delivery, and discuss the bedside approach to assessing the adequacy of oxygen delivery in critically ill patients. Although there have been technological advances in the assessment of oxygen delivery, we revisit and emphasize the importance of a 'tried and true' method – the physical examination. Also potentially important in the evaluation of oxygen delivery is the utilization of biomarkers (e.g., lactate, ScvO2, NIRS). In complementary fashion, bedside ultrasound for hemodynamic assessment may augment the physical examination and biomarkers, and represents a potentially important adjunct for assessing the adequacy of oxygen delivery.